A novel raffinose biological pathway is observed by symbionts of cotton≡Verticillium dahliae to improve salt tolerance genetically on cotton. (11th October 2021) - Cui, Ruifeng; Lu, Xuke; Chen, Xiugui; Malik, Waqar Afzal; Wang, Delong; Wang, Junjuan; Wang, Shuai; Guo, Lixue; Chen, Chao; Wang, Xiaoge; Wang, Xinlei; Dai, Maohua; et al.
Abstract: Verticillium dahliae is a soil‐borne, phytopathogenic fungus that causes Verticillium wilt in cotton. Salt tolerance of cotton plants suffering from Verticillium wilt was significantly improved, but the mechanism is unknown. In this study, we built a symbiont named Cotton≡VD by immersing cotton plant roots into Verticillium dahliae liquid for four days. This resulted in a strong interaction between hyphae and the cotton roots. Under NaCl treatment for 24 h, the Cotton≡VD displayed less leaf wilting and improved root growth compared with the control. Biochemical tests of SOD, POD and CAT showed significant overexpression in Cotton≡VD compared with CK. RNA‐seq data analysis of Cotton≡VD indicated a novel 'galactose metabolism pathway' in the KEGG database, in which two key genes, GolS2 and RFS5, were significantly differentially expressed. Symbiotic metabolites inositol galactosyl could be transformed into raffinose to scavenge free radicals and participate in plant osmotic regulation to alleviate salt stress in Cotton≡VD. Functional analysis indicated that silencing of the target gene GhRFS ( RFS5 ) led to a decrease of raffinose content and salt tolerance as compared with CK. Cotton≡VD can significantly improve cotton seedling salt tolerance through improving raffinose content, providing new insights into the salt tolerance mechanism and new salt‐tolerant material in the future.